The effect of level of nutrition before mating, during pregnancy and during lactation on oestrus, ovulation and the fertility of the ewe - Meaker, Helgaard Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1970.